2020
DOI: 10.1063/5.0032494
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the conductive filament with cycling in TaOx-based resistive switching devices

Abstract: Physical changes occurring in TiN/TaO2.0±0.2/TiN resistive random-access memory devices after prolonged cycling have been analyzed by two scanning transmission electron microscopy modalities: high angle annular dark field and x-ray energy dispersive spectroscopy. In just formed devices, filaments had a shape of a 10 nm diameter Ta-enriched column with the O-rich gap next to electrodes, which was positively biased during electroformation. Devices that failed by stuck-in-high resistance state mode exhibited Ta d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…On the one hand, the irreversible change of resistance to HRS (clearly visible in Figure 7 d for memristors grown in CB) may be correlated to a phase segregation process, in which the number of metallic Nb-rich regions decreases, being progressively isolated by the local increase in the O in the matrix. On the other hand, the end of device lifetime may be also justified by the formation of O-enriched gaps in the CFs at the interfaces of the electrodes, thus leading to permanent switching to HRS during consecutive pulsing [ 49 ]. However, the top electrode material is crucial for defining the maximum number of switching cycles in bipolar devices since O migrates from the interface to the bulk, thus forming O reservoirs near Pt interface accumulating after each set to HRS.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, the irreversible change of resistance to HRS (clearly visible in Figure 7 d for memristors grown in CB) may be correlated to a phase segregation process, in which the number of metallic Nb-rich regions decreases, being progressively isolated by the local increase in the O in the matrix. On the other hand, the end of device lifetime may be also justified by the formation of O-enriched gaps in the CFs at the interfaces of the electrodes, thus leading to permanent switching to HRS during consecutive pulsing [ 49 ]. However, the top electrode material is crucial for defining the maximum number of switching cycles in bipolar devices since O migrates from the interface to the bulk, thus forming O reservoirs near Pt interface accumulating after each set to HRS.…”
Section: Resultsmentioning
confidence: 99%
“…[5] In these devices, the electrical field reversibly modifies the resistance of an oxide electron microscopy showed an accumulation of Ta within filaments rather than a depletion of oxygen. [14,17,18] Some studies even conclude that the filament contains metallic Ta clusters. [15] Such discrepancies indicate that the filament formation is a complex process that is affected by a manifold of experimental conditions, such as electrical biasing procedure, TaO x thin film stoichiometry and thickness as well as electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, spectromicroscopic methods, such as transmission electron microscopy (TEM) based electron energy loss and energy dispersive X-ray spectroscopy, have been employed to study conductive filaments in TaO x devices. [14,17,18,24] However, the drawback of these techniques is that they measure the elemental distribution throughout the whole sample thickness, i.e., the TEM lamella. This impedes a direct assessment of the filament composition.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al reported that repeated switching operation can cause phase segregation in the active layer, resulting in resistive switching failure by stuck-in-HRS, which is similar here. 49 There is still room to improve the endurance of the device for practical application. Future work is necessary to improve the device endurance for practical applications, such as the electronic packaging process (prevent the damage of humidity and oxygen), optimization of the active layer (such as thickness, roughness, crystal phase, etc.…”
Section: Resultsmentioning
confidence: 99%